Bioaugmentation of anaerobic fungus Orpinomyces joyonii boosts sustainable biomethanation of rice straw without pretreatment. (July 2020) - Shetty, Deepa; Joshi, Akshay; Dagar, Sumit Singh; Kshirsagar, Pranav; Dhakephalkar, Prashant K.
Abstract: Rice straw is an abundant, renewable and energy rich agricultural biomass. Energy recovery in the form of biomethane from rice straw can be a sustainable process. However, one of the drawbacks associated with this process is the recalcitrant nature of rice straw which necessitates energy intensive, expensive and polluting thermochemical pretreatment of the substrate. Fiber digesting anaerobic fungi have the ability to degrade the plant biomass. Hence, the present investigation was undertaken to enhance the biodegradation and subsequently the biomethanation of rice straw by supplementing the startup inoculum with anaerobic fiber digesting fungus, Orpinomyces joyonii . The average daily biogas and methane yield increased by 25.04% and 38.41% respectively over control reactor when the startup inoculum was supplemented with O. joyonii in the test reactor. The reduction in volatile solids, cellulose and hemicellulose components of rice straw during biomethanation process was observed to be 68%, 82%, and 97%, respectively. Orpinomyces joyonii supplementation of startup inoculum enhanced the biodegradation of lignocellulosic component and biomethane yield by anaerobic digestion of rice straw without thermochemical pretreatment. Highlights: Enhanced biomethanation of rice straw with O. joyonii augmentation is illustrated. O. joyonii facilitated >80% degradation of cellulose and hemicellulose during AD. 315 L CH4 /kg VS of rice straw was obtained without thermochemical pretreatment. Methane yield in digester operated in steady state was >95% of theoretical yield.